The The Effect of Tax Avoidance and Leverage on Company Value: Case Study on a Financial Sub-Sector Service Company Listed on Indonesia Stock Exchange for 2018 – 2022 Period - Sysfahrina, Sysfahrina (Journal of Business Management and Economic Development, 2024)
This study aims to examine the effect of tax avoidance and leverage on company value. The research method used, which uses a quantitative descriptive approach method. Data testing was performed using Panel Data Regression Analysis. This data analysis technique is processed with EViews 12 SV software for Windows. Tax avoidance has no significant effect on the value of the company with a percentage value of 45%. Leverage has a significant effect on the value of the company with a percentage value of -5.51%. The variables Tax avoidance and leverage show prob. (F-statistic) is smaller than 0.05 so that is rejected so that together (simultaneously) it affects the value of the company.